Malaysian public school libraries / Roziya Abu - Abu, Roziya (Universiti Teknologi MARA, Kedah, 2017)
School libraries are believed to have positive impacts on students' achievement. It is said that a strong library program that is adequately staffed, resourced and funded can lead to a higher student achievement regardless of their parents socioeconomic or educational levels as well as the local community demographic background. Thus, these achievements must in one way or another link with the quality of the collection of the school library and its success in integrating information literacy into the school curriculum. This attainment will determine students' mastery of both content and information seeking skills. Furthermore, an effective school library management and resources, is believed in making positive differences to students' self-esteem, confidence, independence and sense of responsibility regarding their own learning efforts. Nevertheless, the context in which school librarians and teacher librarians operate today has changed significantly. In Malaysia particularly, there has been a very low numbers of qualified teacher librarians employed in public school libraries. Hence, explosions in information production and the development of information communication technologies (ICTs); changes in educational philosophy and practice, including a greater focus on learning outcomes,inquiry-based learning, evidence-based practice and school accountability; and changes in the nature and role of the teacher librarian because of these developments, is making it harder for our local school libraries. These recent challenges and trends suggest that a review of literature on the impact of school libraries on students' achievement in Malaysian context is urgently needed. This paper will investigate the current state of Malaysian public-school libraries - its usage, its impact and its future in relation to endorsing young Malaysia Highfliers.